A NEW APPROACH TO THE LYRICAL ELEMENT IN BLANCA VARELA FROM THE POINT OF VIEW OF BAROQUE STYLE - Horna, Martin (2013)
This article shows how the baroque style enriches the poetry of Blanca Varela. This relation has received little attention and, in fact, has hardly been noticed in studies on the subject. Other aspects, existentialist themes, the predominance of antithesis, the contrasts between light and shade, grotesque allusions, skepticism about truth and reality, are all present in the work of Varela, but the baroque style is one of its earliest points of reference. In this study we will see the conceptual attributes, the influence of Quevedo or her relation with purely baroque symbols, and also at the same time a certain relationship with painting will be noted in the writer. Even though this aspect has already been seen by few people, very little has been said about the purely artistic aspects of baroque or above all of the important presence of its vanity.